WHEN RESILIENCE EXCLUDES: GENDERED POWER, INTERSECTIONALITY, AND COMMUNITY-BASED DISASTER RISK REDUCTION IN COASTAL INDONESIA - I Putu Yoga Bumi Pradana; Rudi Rohi; Angel Christy Patricia (Magister Ilmu Administrasi Publik, 2025)
This study examines how social, cultural, and institutional configurations shape women’s participation in community-based disaster risk reduction (CBDRR) in coastal Kupang, Indonesia. Despite formal commitments to gender inclusion in disaster governance, women’s participation remains uneven and highly context-dependent. Using a qualitative comparative case study of Kelurahan Lasiana and Kelurahan Oesapa Barat, the research draws on in-depth interviews, focus group discussions, participant observation, and document analysis to explore multi-layered participation dynamics. The findings reveal that entrenched gender norms, time poverty, and hierarchical power relations continue to limit women’s engagement in CBDRR. In both communities, caregiving responsibilities and mobility restrictions reinforce women’s peripheral roles in formal DRR spaces. Cultural configurations act as a double-edged sword: while women’s local knowledge is widely valued informally, patriarchal authority structures and conservative adat and religious narratives constrain their leadership and decision-making influence. Institutionally, a significant gap persists between formal participation mandates and substantive influence. However, Lasiana demonstrates greater progress through supportive leadership, cultural reframing, and participatory innovations such as community mapping and oral histories. In contrast, Oesapa Barat exhibits more rigid cultural scripts and institutional inertia that confine women’s roles to symbolic functions. This study’s novelty lies in its integrative analytical framework and comparative design. It offers new insights into how enabling and constraining dynamics interact across social, cultural, and institutional domains to shape gendered resilience governance